Galactosyltransferase activity is not localized to the brush border membrane of human small intestine. Issue 2 (February 1986) - Boyle, Frances; Snape, Susan; Duane, Paul; Cook, Neil; Peters, Timothy
Abstract : A recent report [Roth et al. (1985) J. Cell Biol. 100 : 118–125], using immunocytochemical techniques, calimed that human duodenal galactosyltransferase is located predominantly on the external aspect of enterocyte brush border membranes. Analytical subcellular fractionation by sucrose density gradient centrifugation of human jejunum biopsy homogenates demonstrated that galactosyltransferase activity is localized to the Golgi fraction (equilibrium density of 1.14 g cm −3 ) and is not found in significant amounts in the brush border membrane (equilibrium density of 1.22 g cm −3 ).